Experimental study on the diesel and biodiesel spray characteristics emerging from equilateral triangular orifice under real diesel engine operation conditions. (15th July 2018) - Yu, Shenghao; Yin, Bifeng; Deng, Weixin; Jia, Hekun; Ye, Ze; Xu, Bin; Xu, Huaping
Highlights: Both diesel and biodiesel issuing from triangular orifice underwent axis-switching. High backpressure can inhibit the spray axis-switching for diesel and biodiesel. The triangular diesel spray was much easier to undergo axis-switching than biodiesel. Larger spray width and cone angle for diesel indicated better air-fuel mixing quality. Abstract: The triangular spray has a potential to accelerate air-fuel mixing rate and undergo axis-switching during the injection process, which both are beneficial for improving the atomization quality. This paper presents an experimental investigation on the macro-spray characteristics and the mechanism of axis-switching with diesel and biodiesel emerging from equilateral triangular orifice of diesel nozzle, by using shadowgraph technique, under various injection pressures (50 MPa, 70 MPa, 90 MPa) and backpressures (1 MPa, 2 MPa, 3 MPa). Two CCD cameras were set to capture the macro spray images at the minor and major view planes simultaneously. Macro spray characteristics values were processed from the spray images in different view planes by MATLAB. The results indicated that the spray width of biodiesel was larger than that of diesel at all conditions from all view planes. In addition, both diesel and biodiesel emerging from equilateral triangular orifice underwent axis-switching during the spray progress even under the typical diesel engine operation conditions. Moreover, the difference of equilateral triangular spray widths between minor plane and major plane decreases as the backpressure increases for both fuels, it is expected that the increasing of backpressure enhances the aerodynamic effects, resulting in inhibiting the spray axis-switching. Furthermore, the difference of diesel spray widths between the major plane and minor plane was much higher than that of biodiesel. Because the higher surface tension and viscosity of biodiesel can cause smaller surface-instabilities and also resist the spray deformation, which are conductive to suppress the biodiesel spray axis-switching, and thus ultimately lead to narrowing the difference of biodiesel spray widths between minor plane and major plane. Finally, the spray tip penetration of biodiesel was consistent longer than that of diesel, while the spray cone angle of biodiesel was smaller than that of diesel, and also there was an interaction between major and minor view planes for diesel spray cone angle values at the backpressure of 1 MPa, but it didn't happen for biodiesel during the whole injection process. The present results indicated that the diesel spray was much easier to undergo axis-switching. The higher probability of axis-switching, larger spray cone angle and spray width of diesel demonstrated better air-fuel mixing quality than biodiesel.